IMPLEMENTASI TRANSISI PAUD KE SD DALAM MEMBANGUN FASE FONDASI ANAK USIA DINI - Arina Qisthi Fakhrunnisa; Tri Yuni Hendrowati; Fatqul Hajar Aswad (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the implementation of the Early Childhood Education (PAUD) to Primary School (SD) transition in building the foundational phase of early childhood education, focusing on learning practices, the use of initial assessment, and cross-level collaboration to support children’s holistic readiness. Methods: The study employed a qualitative approach using a case study design. The research was conducted at one PAUD institution and two public primary schools in Bandar Lampung, Indonesia. Data were collected through observations, in-depth interviews with principals, teachers, and parents, as well as document analysis. Data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing, supported by source and method triangulation. Results: The findings indicate that schools have begun implementing the PAUD–SD transition policy by eliminating early literacy and numeracy tests, applying child-friendly school orientation programs, and adjusting learning environments. The development of foundational competencies primarily emphasizes social-emotional skills, independence, and character building, while the use of initial assessment data and formal PAUD–SD collaboration remains limited. Novelty: This study provides empirical evidence on the operationalization of the foundational phase at the school level by highlighting the role of school management and stakeholder collaboration.